2013
DOI: 10.1371/journal.pone.0081798
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is Associated with Lower Coronary Microvascular Density

Abstract: BackgroundObesity is associated with diastolic dysfunction, lower maximal myocardial blood flow, impaired myocardial metabolism and increased risk of heart failure. We examined the association between obesity, left ventricular filling pressure and myocardial structure.MethodsWe performed histological analysis of non-ischemic myocardium from 57 patients (46 men and 11 women) undergoing coronary artery bypass graft surgery who did not have previous cardiac surgery, myocardial infarction, heart failure, atrial fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 46 publications
1
39
0
1
Order By: Relevance
“…Impaired HIF signalling would down‐regulate angiogenesis, ultimately resulting in reduced capillary density in the heart. Recently, histological analysis of non‐ischaemic myocardium from patients undergoing coronary artery bypass surgery showed that obesity was associated with lower coronary microvascular density . A previous study from our lab showed that overexpression of angiopoietin 1 improved capillary density in ischaemia‐induced obese db/db mouse hearts via up‐regulating HIF‐1α expression .…”
Section: Discussionmentioning
confidence: 91%
“…Impaired HIF signalling would down‐regulate angiogenesis, ultimately resulting in reduced capillary density in the heart. Recently, histological analysis of non‐ischaemic myocardium from patients undergoing coronary artery bypass surgery showed that obesity was associated with lower coronary microvascular density . A previous study from our lab showed that overexpression of angiopoietin 1 improved capillary density in ischaemia‐induced obese db/db mouse hearts via up‐regulating HIF‐1α expression .…”
Section: Discussionmentioning
confidence: 91%
“…Patients with HFpEF had higher body mass index than controls, and the findings of Mohammed et al are in agreement with the reported association of obesity with reduced microvascular density and increased pulmonary capillary wedge pressure in patients with coronary artery disease undergoing coronary artery bypass graft surgery. 2 Moreover, the inverse association between coronary microvascular density and pulmonary capillary wedge pressure in these patients with coronary artery disease provides support for a role for reduced microvascular density in increased left ventricular filling pressures. 2 Mohammed et al discuss the possible contribution of microvascular destruction and insufficient angiogenesis to the lower microvascular density of HFpEF patients.…”
Section: To the Editormentioning
confidence: 91%
“…2 Moreover, the inverse association between coronary microvascular density and pulmonary capillary wedge pressure in these patients with coronary artery disease provides support for a role for reduced microvascular density in increased left ventricular filling pressures. 2 Mohammed et al discuss the possible contribution of microvascular destruction and insufficient angiogenesis to the lower microvascular density of HFpEF patients. However, they do not consider the role of cardiomyocyte size in determining microvascular density.…”
Section: To the Editormentioning
confidence: 91%
See 1 more Smart Citation
“…leptin, tumour necrosis factor‐α, interleukin‐1β and interleukin‐6), particularly from fat depots surrounding visceral organs . Acting in a paracrine manner, these adipocytokines can cause microcirculatory rarefaction and fibrosis of underlying organs, especially the heart and kidneys . Interestingly, chronic systemic inflammatory states other than obesity (e.g.…”
Section: Evolution Of Obesity‐related Heart Failure With Preserved Ejmentioning
confidence: 99%